Co-infection of Influenza B and Streptococci causing severe pneumonia and septic shock in healthy women - Hirsch Hans H; Bucher Evelyne; Weisser Maja; Aebi Timothy; Marsch Stephan; Siegemund Martin (BMC Infectious Diseases, 2010)
Abstract Background Since the Influenza A pandemic in 1819, the association between the influenza virus and Streptococcus pneumoniae has been well described in literature. While a leading role has been so far attributed solely to Influenza A as the primary infective pathogen, Influenza B is generally considered to be less pathogenic with little impact on morbidity and mortality of otherwise healthy adults. This report documents the severe synergistic pathogenesis of Influenza B infection and bacterial pneumonia in previously healthy persons not belonging to a special risk population and outlines therapeutic options in this clinical setting. Case Presentation During the seasonal influenza epidemic 2007/2008, three previously healthy women presented to our hospital with influenza-like symptoms and rapid clinical deterioration. Subsequent septic shock due to severe bilateral pneumonia necessitated intensive resuscitative measures including the use of an interventional lung assist device. Microbiological analysis identified severe dual infections of Influenza B with Streptococcus pyogenes in two cases and Streptococcus pneumoniae in one case. The patients presented with no evidence of underlying disease or other known risk factors for dual infection such as age (< one year, > 65 years), pregnancy or comorbidity. Conclusions Influenza B infection can pose a risk for severe secondary infection in previously healthy persons. As patients admitted to hospital due to severe pneumonia are rarely tested for Influenza B, the incidence of admission due to this virus might be greatly underestimated, therefore, a more aggressive search for influenza virus and empirical treatment might be warranted. While the use of an interventional lung assist device offers a potential treatment strategy for refractory respiratory acidosis in addition to protective lung ventilation, the combined empiric use of a neuraminidase-inhibitor and antibiotics in septic patients with pulmonary manifestations during an epidemic season should be considered.